PENERAPAN INTERNAL PROCEDURE SYSTEM TERHADAP EFEKTIVITAS PELAYANAN PADA PERUSAHAAN JASA EKSPOR LAUT - Reza Fauzi Jaya Sakti; Elva Fauzia (Institut Transportasi dan Logistik Trisakti, 2017)
PT. Mitsui O.S.K Lines Logistics Indonesia is a freight forwarding company engaged in export and import activities. The main issue studied in this research is whether or not the application of Job Description and Internal Procedure System affect the effectiveness of sea export services. The purpose of this study is to find out and analyze the relationship between job description and internal procedure system applied to the effectiveness of sea export services. In this study, the researchers use multiple regression analysis techniques, multiple correlation, coefficient determinant, and hypothesis testing. The results of the analysis and discussion show the existence of positive and strong influence on the job description implementation and Internal Procedure System towards the Effectiveness of Sea Export Services. This is shown by multiple linear regression equation Y = 1,463 + 0.379.X_1 + 0.553.X_2, correlation coefficient equals to 0,769 and coefficient determinant equals to 59.13%. Hypothesis test also shows that F stat > F table (20,9 > 3,3) then Ho is rejected and Ha is accepted. There is a significant relation between job description implementation and internal procedure system towards the effectiveness of service export of sea at PT. Mitsui O.S.K Lines Logistics Indonesia.